The Comparison of Antibacterial Activities of Soursop Leaf (Annona muricata L.) and Basil Leaf (Ocimum americanum L.) Ethanolic Extracts on Gel Formulated Against Staphilococcus aureus and Propionibacterium acnes - Efendy, Ismail; Rumanti, Ruth Mayana; Rimala, Mutia; Ginting, Indra; Simarmata, Yettrie Bess Congencya; Diana, Vivi Eulis (Asian Journal of Pharmaceutical Research and Development, 2020)
Objectives: The purpose of this study was to determine antibacterial activity of Soursop leaf (Annona muricata L.) and Basil leaf (Ocimum americanum L.) ethanolic extract on gel formulated againts Staphilococcus aureus and Propionibacterium acnes. Design: This study uses an experimental laboratory design. This research uses difusion method, the inhibitory comparison between positive and negative control performed. This study compared the antibacterial activity of two gels that have different active ingredients to the growth of skin bacteria, namely Staphilococcus aureus and Propionibacterium acnes. Interventions: The sample used was two types of gels each containing Soursop leaf and basil leaf ethanol extract that in various concentration of 5, 10 and 15%. As a comparison, Clindamycin gel concentration 1% was used. The distilled water was used as a negative control. Main outcome measure: The results showed a significant difference in inhibition between the samples groups against negative controls. The inhiibitory zone diameter of soursop leaf in 5, 10, and 15% concentrations were 9.30+0.17, 10.37+0.63, and 12.27+0.27 mm in inhibiting the growth of Staphilococcus aureus, and 9.00+0.00, 10.40+0.20, and 12.07+0.13 mm in inhibiting Propionibacterium acne. The result of the basil gel were 10.37+0.82, 11.50+0.50 and 12.43+0.29 against Staphilococcus aureus and 10.90+0.38, 12.00+0.00 and 13.37+0.20 against Propionibacterium acnes. Conclusion: The both gels containing soursop and basil leaves ethanol extract have good antibacterial activity.